Potential Herb-Drug Pharmacokinetic Interactions between African Wild Olive Leaf Extract and Selected Antihypertensive Drugs - Mmopele, Katlego; Combrinck, Sandra; Hamman, Josias; Willers, Clarissa; Chen, Weiyang; Viljoen, Alvaro (Planta Medica, 2018)
The African wild olive (Olea europaea subsp. africana) is traditionally used as a hypotensive agent. Herb-drug interactions may result from the concurrent use of herbal medicines and conventional prescription drugs. This aspect was investigated by determining the effect of the extract on the in vitro intestinal epithelial permeation of selected hypotensive drugs using the Caco-2 cell culture model. The phytochemical profiles of leaf extracts of African wild olive from different localities in South Africa were compared, since efficacy is determined by the chemical composition. Extracts were analysed using ultra-performance liquid chromatography. The oleuropein concentration varied considerably from below the detection limit (4.94 µg/mL) to 59.4 mg/g dry weight. Chemometric models constructed from the aligned chromatographic data indicated only quantitative differences between the profiles. The leaf extract was found to increase the permeability of propranolol in the absorptive direction (Papp = 8.93 × 10−6 cm/s) across Caco-2 cell monolayers, but considerably decreased transport in the secretory direction (Papp = 3.68 × 10−6 cm/s). The permeation of diltiazem was enhanced by the extract in both the absorptive (Papp = 7.33 × 10−6 cm/s) as well as in the secretory direction (Papp = 7.16 × 10−6 cm/s), but a decrease in the efflux ratio was observed. The extract therefore caused a net increase in the transport of both drugs in the absorptive direction due to an inhibition effect on their efflux. This suggests a potential increase in the blood levels of these drugs when taken simultaneously with African wild olive leaf extract, indicating potential adverse effects that must be verified in vivo.
Keywords: Olea europaea subspecies africana; Oleaceae; herb-drug interaction; oleuropein; antihypertensive drugs; Caco-2 cells